γδ T cell-intrinsic IL-1R promotes survival during Staphylococcus aureus bacteremia - Wang, Yu; Ahmadi, Michael Z.; Dikeman, Dustin A.; Youn, Christine; Archer, Nathan K. (Frontiers in Immunology, 2023)
Staphylococcus aureus is a leading cause of bacteremia, further complicated by the emergence of antibiotic-resistant strains such as methicillin-resistant S. aureus (MRSA). A better understanding of host defense mechanisms is needed for the development of host-directed therapies as an alternative approach to antibiotics. The levels of IL-1, IL-17, and TNF cytokines in circulation have been associated with predictive outcomes in patients with S. aureus bacteremia. However, their causative role in survival and the cell types involved in these responses during bacteremia is not entirely clear. Using a mouse model of S. aureus bacteremia, we demonstrated that IL-17A/F and TNF had no significant impact on survival, whereas IL-1R signaling was critical for survival during S. aureus bacteremia. Furthermore, we identified that T cells, but not neutrophils, monocytes/macrophages, or endothelial cells were the crucial cell type for IL-1R-mediated survival against S. aureus bacteremia. Finally, we determined that the expression of IL1R on γδ T cell, but not CD4+ or CD8+ T cells was responsible for survival against the S. aureus bacteremia. Taken together, we uncovered a role for IL-1R, but not IL-17A/F and TNF in protection against S. aureus bacteremia. Importantly, γδ T cell-intrinsic expression of IL-1R was crucial for survival, but not on other immune cells or endothelial cells. These findings reveal potential cellular and immunological targets for host-directed therapies for improved outcomes against S. aureus bacteremia.